Animal microbiome
Animal Microbiome will address all aspects of non-human animal-associated microbiomes, including (but not limited to): domestic, wild and livestock animals. We will also welcome studies encompassing (but not limited to): marker gene surveys; '-omics' surveys (including culturomics, metagenomic, metatransciptomic, metaproteomic, and metabolomic), bioinformatic and other analytical tools, which have an underlying strong hypothesis for using such techniques.